The effect of biography intervention on the ageism of Coronary Care Unit (CCU) nurses: a Randomized Clinical Trial - Melika BagheriAzad; Nayyereh Davoudi; Vahid Ghavami; Fatemeh Esmaelzadeh (BMC Geriatrics)
Abstract Background Ageism toward older adults is a global concern with significant negative effects on both individuals and society, leading to early loss of independence, increased disability, and higher mortality rates among older adults. This study aimed to evaluate the effect of biographicay intervention on reducing ageism among coronary care unit (CCU) nurses. Methods This randomized controlled trial with a pretest-posttest design was conducted on 65 nurses working in CCUs in Mashhad, Iran. Participants were selected through convenience sampling, and hospitals were randomly assigned as intervention and control groups. Both groups received in-person training on the concept of ageism and positive aging. In the intervention group, the researcher conducted interviews with hospitalized older adults over six weeks to gather biographical information, which was then shared with the nurses. Before and after the intervention, participants completed the Ageism Scale for Nurses in Hospital Environments. Data were analyzed using SPSS version 22. Results No significant difference in ageism scores was observed between the intervention and control groups before the intervention. However, after the intervention, a statistically significant reduction in ageism scores was observed in the intervention group compared to the control group (p < 0.001). Conclusion The biographical intervention effectively reduced ageism among CCU nurses. Increased knowledge of the various dimensions of older adults’ lives seems to have positively influenced nurses’ attitudes and fostered appropriate interactions, ultimately facilitating care and treatment. Trial Registration The article was registered by the Iranian Registry of Clinical Trials under number IRCT20220522054956N1, date of registration 2022/07/02.